Can multiple-target search paradigms reliably discriminate serial and parallel search processes? - Zheng, Yujie; Pan, Yuhang; Xu, Yinuo; Li, Zhi (Quarterly Journal of Experimental Psychology, 2026)
Distinguishing between serial and parallel processing modes in visual search tasks remains a challenge in cognitive psychology. The multiple target search (MTS) paradigm, which utilizes target redundancy gains to identify parallel searches, is currently one of the promising approaches for this distinction. Despite being proposed five decades ago, this method has not gained widespread acceptance among researchers in visual search area, potentially due to two limitations. One is its inability to reliably detect redundancy gains in established parallel searches (e.g., the distinct popout color search). The other is the presence of redundancy gains in pure-target-absent trials, which are apparently incompatible with the MTS's explanation of redundancy gains. In this study, we tested a modified version of the traditional reaction-time-based MTS (rt-MTS) by developing an accuracy-based MTS (acc-MTS). The results suggested that the acc-MTS successfully overcomes the aforementioned limitations of the rt-MTS paradigm while maintaining significantly greater efficiency. These findings established the acc-MTS as a reliable and efficient methodological advancement for determining the serial or parallel nature of visual search tasks.